Personal factors associated with pre-competitive anxiety in elite gymnasts - Pineda-Espejel, H. A.; Alarcón, E.; Trejo, M.; Chávez, C.; Arce, R. (Science of Gymnastics Journal, 2016)
The aim of this study was to analyze how goal orientations and two facets of perfectionism -striving for perfection and negative reactions to imperfection- be related to precompetitive anxiety in elite gymnasts. Thirty seven artistic gymnasts answered a series of questionnaires to measure the study variables. The results showed that cognitive anxiety was related to negative reactions to imperfection, while the self-confidence was predicted by the task orientation. In conclusion, aspects of personality, such as task orientation and negative reactions to imperfection, anticipate the cognitive self-confidence and anxiety, respectively, at the time previous to a senior gymnastics competition.